Efforts of BKPSDM Padang City in Fulfilling Staffing Needs Based on Workload Analysis in Padang City Government - Amalia, Syafa Hanni; Putri, Nora Eka (The Future of Education Journal, 2025)
This study aims to examine the efforts of the BKPSDM of Padang City in meeting the staffing needs based on the workload analysis in the Padang City Government. The method used is descriptive qualitative with data collection techniques through interviews and documentation. Data were analyzed using reduction techniques, data presentation, and conclusion drawing based on the theory of George C. Edward III, which includes aspects of communication, resources, disposition, and bureaucracy structure. The research findings show that the BKPSDM of Padang City in fulfilling staffing needs adheres to the Anjab ABK (Analysis of Workload and Job Descriptions). In its implementation, it is based on Government Regulation Number 17 of 2020. Fulfilling staffing needs is an implementation of Law Number 20 of 2023 on State Civil Apparatus. Based on George C. Edward III’s theory, the indicators are still not optimal in the implementation of ASN recruitment policies. This is due to the frequent changes in the central government’s policy on employee procurement, which leads to a lack of communication with the Regional Device Organizations in Padang City. The findings indicate the need for enhanced coordination and communication in ASN procurement in Padang City. This study is expected to provide recommendations to relevant parties in improving the implementation of ASN recruitment in Padang City.